Effect of pretreated zeolite media in removal of landfill leachate pollutants - Ragunathan, Santiagoo; Naimah, Ibrahim; Azlinda, Abdul Ghani; Nurul Izza, Abd Hamid (Malaysia Institute of Chemistry, 2008)
Organized by Malaysia Institute of Chemistry, 23rd - 25th August 2007 at Putra World Trade Centre, Kuala Lumpur.